A Catenane Assembled through a Single Charge‐Assisted Halogen Bond1. Issue 16 (11th March 2013) - Gilday, Lydia C.; Lang, Thomas; Caballero, Antonio; Costa, Paulo J.; Félix, Vítor; Beer, Paul D.
<x xml:space="preserve">Abstract</x> Getting connected: The formation of pseudorotaxane assemblies between a designed macrocyclic halogen bonding (XB) acceptor (red in scheme) and a series of XB donor threading components was templated by a single halogen bond. The strength of the XB assembly between the pyridine macrocycle and iodopyridinium thread was utilized in the ring‐closing metathesis clipping synthesis of a [2]catenane.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>